GENOTYPING OF CLOSTRIDIUM PERFRINGENS FROM FRESH WATER FISH AND FISH PICKLES - Das, Arunava; Jain, Adarsh (Journal of microbiology, biotechnology and food sciences, 2012)
This study aims to evaluate the genotypes of Clostridium perfringens in fish and fish based products from Tamil Nadu and Kerala states of India. A total of 301 samples consisting intestinal contents of freshwater fish (234) from various dams, freshwater lakes, ponds, retail shops and markets and fish pickles (67) obtained from randomly selected retail shops and supermarkets were investigated. Bacterial isolations, identifications and phenotypic characterization of virulence factors were carried out as per standard microbiological procedures. Genotyping of the C. perfringens isolates were done by amplifying four major lethal toxin genes namely- alpha toxin gene (cpa), beta toxin gene (cpb), epsilon toxin gene (etx), iota toxin gene (iA) in a Thermal Cycler. Isolates were also screened for the presence of enterotoxin gene (cpe) and beta2 toxin gene (cpb2) by single step PCR. Biochemical tests and phenotypic determination of virulence factors tentatively identified 82 (27.24%) isolates of C. perfringens. In PCR assay, all 82 (100%) isolates harbored cpa toxin genes of C. perfringens, however, 65 (79.26%) isolates also carried additional cpb2 toxin genes. None of the isolates were found positive for beta, epsilon, iota and enterotoxin genes. Genotyping of the 82 isolates by PCR revealed that all the isolated bacteria were belonged to C. perfringens type A and both cpa and cpb2 toxin genes were prevalent among the isolates of C. perfringens type A, impending the risk of pathogenicity to human via freshwater fish and fish pickles.